VALIDITAS LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS INKUIRI TERBIMBING UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI LAJU REAKSI - Sulasni, Dea (rc-institut, 2019)
Chemistry is an abstract and complex science. Chemical material was studied in the second semester of class XI. The reaction rate addresses the concept of reaction rate, collision theory, factors that influence the reaction rate, the reaction rate equation and the reaction order. This study aims to look at the validity of guided inquiry-based student worksheets to develop critical thinking skills. based on the results of the study the average validity of 0.86. so that it can be concluded that the student worksheet is very valid.